Empirical Economic and Financial Research - Theory, Methods and Practice

Introduction - Beran, Jan; Feng, Yuanhua; Hebbel, Hartmut (Empirical Economic and Financial Research)

An iterative plug-in algorithm for realized kernels - Feng, Yuanhua; Zhou, Chen

Uncertainty in Weighting Formulary Apportionment Factors. How Does Weighting Uncertainty Impact After-Tax Income of Multinational Groups?, - Ortmann, Regina
Formulary apportionment is an intensively debated mechanism for allocating tax base within multinational groups. Systems under which the formula is identical in all jurisdictions and systems under which jurisdictions can determine the weights on the formula factors individually can be observed. The latter systems produce uncertainty about the overall tax-liable share of the future group tax base. Counter-intuitively, I identify scenarios under which increased uncertainty leads to higher expected future group income. My results provide helpful insights for firms and policy makers debating the specific design of a formulary apportionment system.

Formula Apportionment or Separate Accounting? Tax-Induced Distortions of Multinationals' Locational Investment Decisions - Ortmann, Regina; Pummerer, Erich

Entscheidungskalküle US-amerikanischer Unternehmen bei Tax Inversions. What Drives the Decision of U.S. Firms to Expatriate? - Oßwald, Benjamin; Sureth-Sloane, Caren (Steuer und Wirtschaft International)

Investment Effects of Wealth Taxes under Uncertainty and Irreversibility - Niemann, Rainer; Sureth-Sloane, Caren

Hold or Sell? How Capital Gains Taxation Affects Holding Decisions - Hegemann, Annika; Kunoth, Angela; Rupp, Kristina; Sureth-Sloane, Caren

The Effect of Taxes on Corporate Financing Decision - Evidence from the German Interest Barrier - Alberternst, Stephan; Sureth-Sloane, Caren

Managing the bright and dark sides of status endowment in hierarchical loyalty programs - Eggert, Andreas; Steinhoff, Lena; Garnefeld, Ina (Journal of Service Research)